Cardiovascular toxicity induced by immunotherapy in non-small cell lung cancer: a systematic review and meta-analysis of observational studies - Sabaté-Ortega, Josep; Teixidor-Vilà, Eduard; Sais, Èlia; Hernandez-Martínez, Alejandro; Montañés-Ferrer, Claudia; Coma, Núria; Polonio-Alcalá, Emma; Pineda, Victor; Bosch-Barrera, Joaquim (Frontiers in Oncology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs), an immunotherapy used in cancer treatment, are associated with potential cardiovascular (CV) toxicity. Monitoring CV issues in non-small cell lung cancer (NSCLC) patients is challenging due to their lower incidence and diversity. Hence, enhancing our understanding of CV toxicities in patients receiving ICIs is required to improve their quality of life and survival. Hence, the main objective of this study is the evaluation of CV side effects in ICI-treated NSCLC patients by assessing the prevalence and hazard of CV events.MethodsA systematic review was conducted to identify relevant studies, up to November 21st, 2023. A meta-analysis was performed to examine the data extracted from the selected studies. The random-effects model was applied to account for heterogeneity among studies, reporting results as prevalence rates and hazard ratios (HR) alongside their corresponding 95% confidence intervals (CI). Studies meeting inclusion criteria were selected and outcomes were assessed through qualitative analysis.ResultsTwelve observational studies using Real world Data were included, encompassing 23,621 patients with NSCLC. Our findings indicated that patients treated with ICIs exhibited a 3% prevalence of CV events and a significantly higher hazard (HR = 1.78 (95% CI: 1.46, 2.17); p < 0.00001; I2 = 72%) compared to patients treated with other drugs.ConclusionsThe treatment with ICIs caused a higher rate of CV events compared to non-ICI treatments. Nevertheless, further research is required to elucidate the underlying mechanisms and implications for patient care. This calls for continued research efforts to optimize the cardiovascular health of patients undergoing immunotherapy for lung cancer.